Near‐Bed Turbulent Kinetic Energy Budget Under a Large‐Scale Plunging Breaking Wave Over a Fixed Bar. Issue 2 (24th February 2018) - van der Zanden, Joep; van der A, Dominic A.; Cáceres, Iván; Hurther, David; McLelland, Stuart J.; Ribberink, Jan S.; O'Donoghue, Tom
Abstract: Hydrodynamics under regular plunging breaking waves over a fixed breaker bar were studied in a large‐scale wave flume. A previous paper reported on the outer flow hydrodynamics; the present paper focuses on the turbulence dynamics near the bed (up to 0.10 m from the bed). Velocities were measured with high spatial and temporal resolution using a two component laser Doppler anemometer. The results show that even at close distance from the bed (1 mm), the turbulent kinetic energy (TKE) increases by a factor five between the shoaling, and breaking regions because of invasion of wave breaking turbulence. The sign and phase behavior of the time‐dependent Reynolds shear stresses at elevations up to approximately 0.02 m from the bed (roughly twice the elevation of the boundary layer overshoot) are mainly controlled by local bed‐shear‐generated turbulence, but at higher elevations Reynolds stresses are controlled by wave breaking turbulence. The measurements are subsequently analyzed to investigate the TKE budget at wave‐averaged and intrawave time scales. Horizontal and vertical turbulence advection, production, and dissipation are the major terms. A two‐dimensional wave‐averaged circulation drives advection of wave breaking turbulence through the near‐bed layer, resulting in a net downward influx in the bar trough region, followed by seaward advection along the bar's shoreward slope, and an upward outflux above the bar crest. The strongly nonuniform flow across the bar combined with the presence of anisotropic turbulence enhances turbulent production rates near the bed. Plain Language Summary: The flow of water under wind‐driven waves near the coast is highly energetic, leading to the production of chaotic, "turbulent" fluid motions. Turbulence plays an important role in the flow and the transport of sediment under waves. Therefore, understanding turbulence dynamics is crucial to understanding the behavior of waves and their effects on shoreline processes (e.g., beach erosion). Previous research shows that the breaking of waves leads to a massive production of turbulent energy, but the vertical and horizontal spreading of turbulence is not properly understood. Through experiments in a large‐scale wave flume, using acoustic and laser‐based measurement instrumentation, the behavior of turbulent energy under breaking waves is systematically investigated. Results show that wave breaking alters turbulence dynamics over the full water column, from the water surface all the way down to the bed. Turbulence is spread horizontally and vertically by "undertow" currents generated by the breaking wave. Moreover, wave breaking turbulence leads to the production of additional turbulence in the water column. The new insights in this paper can be used to further develop computational models for the flow and transport of sediment under breaking waves. Key Points: Horizontal and vertical advection, production, and dissipation are the dominant terms in the near‐bed TKE balance A two‐dimensional (horizontal + vertical) clockwise circulation advects wave breaking TKE through the near‐bed layer Flow nonuniformity and the presence of energetic anisotropic wave breaking turbulence enhances near‐bed turbulence production